Adjuvant tamoxifen adherence in men with early‐stage breast cancer. Issue 1 (1st October 2021) - Oke, Oluchi; Niu, Jiangong; Chavez‐MacGregor, Mariana; Zhao, Hui; Giordano, Sharon H.
Abstract : Background: Most breast cancers (BCs) in men are hormone receptor–positive. Adjuvant tamoxifen is part of the standard treatment of these patients. Small, single‐institution studies have suggested that men have high rates of discontinuing adjuvant endocrine treatment. The authors examined rates of tamoxifen discontinuation and medication adherence in a large population‐based cohort of male patients with BC. Methods: In the Surveillance, Epidemiology, and End Results–Medicare database, male patients with invasive nonmetastatic BC, diagnosed between 2007 and 2013, who were ≥65 years old, had Part D coverage, and had tamoxifen prescriptions within 1 year of diagnosis were identified. Adherence was defined as a medication possession ratio of ≥80% among those patients who were filling tamoxifen prescriptions. Logistic regression model was used to assess predictors of tamoxifen adherence. Results: A total of 451 patients met eligibility criteria. The median age at diagnosis was 75 years. The median follow‐up was 32.5 months. The rates of tamoxifen discontinuation were 15.8%, 24.3%, 31.3%, 36.9%, and 48.3% at 1, 2, 3, 4, and 5 years after diagnosis, respectively. Among the men who were still taking tamoxifen, the corresponding adherence rates were 76.9%, 73.6%, 68.7%, 64.8%, and 60.2%. In the adjusted model, significant predictors of lower adherence included residing in a high poverty area (odds ratio [OR], 0.77; 95% confidence interval [CI], 0.28‐2.12) and a Charlson comorbidity score of ≥2 (OR, 0.46; 95% CI, 0.22‐0.97). Conclusion: Older men with breast cancer have high rates of tamoxifen discontinuation, with 48% of all patients discontinuing tamoxifen before the end of year 5. Additionally, even among those patients continuing tamoxifen, a substantial number of patients are nonadherent. Further research should evaluate potentially modifiable reasons for treatment discontinuation and lack of adherence to tamoxifen. Abstract : On the basis of an analysis, older men with breast cancer have high rates of tamoxifen discontinuation, with 48% of all patients discontinuing tamoxifen before the end of year 5. In addition, even among those patients continuing tamoxifen, a substantial number of patients are nonadherent.